THE USE OF YOUTUBE MEDIA THROUGH GROUP DISCUSSION IN TEACHING SPEAKING - Rahmi Akmal Hussin; Sofyan A. Gani; Asnawi Muslem (English Education Journal, 2020)
Possessing adequate English speaking ability is required for senior high school students in Indonesia as shown with the minimum passing criteria of 75 in the National Curriculum (2013). However, the teaching techniques used by teachers are commonly unattractive and monotonous, which therefore affects students’ opportunity to enhance their speaking ability. This study aimed at finding out whether the use of YouTube videos through group discussion assisted students to improve their speaking skills (pronunciation, grammar, vocabulary, fluency and comprehension). The subject of this study was second grade students of two classes of SMA Inshafuddin Banda Aceh, who were chosen by using random sampling technique. The method used in this study was quantitative method with experimental design. The results of this study showed that using YouTube videos through discussion group assisted the students to improve their speaking skills (p0.05), with the most significant improved skill was comprehension. It is, therefore, suggested that teachers consider using YouTube videos in their teaching techniques in an attempt to attract students’ motivation to improve their speaking ability.